Analisis Model Pembelajaran Daring Menggunakan Media PANDAWA - Wijaya, Jevita; Susilo, Herawati; Parno, Parno (University of Muhammadiyah Malang, 2023)
The COVID-19 pandemic has profoundly transformed the landscape of education. Initially, learning activities were face-to-face, then it switched to online activities. Various schools use application programs to assist learning activities between teachers and students. Bani Hasyim Islamic Elementary School developed a media called PANDAWA, which means online student guidelines (Panduan Daring Siswa). Teacher creativity in developing online learning media is interesting to be studied. The research objectives are (1) to describe model instructional using PANDAWA in school. (2) To describe the impact model instructional by using PANDAWA. The research employed descriptive qualitative conducted at SD Islam Bani Hasyim. Sources of data are the school principal, teachers, students and documents. Methods of data collection are namely interviews, observations, questionnaires, and document collection. PANDAWA media was developed by Bani Hasyim Islamic Elementary School teachers from the Google Form application and Microsoft Office PowerPoint. PANDAWA has features ranging from opening, classroom, materials, assignments and closing. Teaching materials are presented in the form of writing, infographics, and videos included in the features. PANDAWA is set with a password or code based on the classroom. Every morning, the teacher gives a code via WhatsApp to the class group to open PANDAWA. The impacts of PANDAWA on learning activities are (1) learning activities are carried out independently, (2) assignment-based activities to students, (3) PANDAWA does not yet have a virtual face-to-face feature; as a result, students only carry out virtual face-to-face meetings 2-3 times a week using the Google Meet, Zoom, and Whatsapp Groups applications, (4) evaluation of student learning cannot yet be detected objectively, (5) students experience boredom which affects student learning interest. PANDAWA makes it administratively more accessible for teachers to collect assignments.